2011
DOI: 10.1007/s00234-011-0996-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparing quantitative tractography metrics of motor and sensory pathways in children with periventricular leukomalacia and different levels of gross motor function

Abstract: Children with bilateral spastic CP with differing levels of gross motor function have corresponding differences detectable on DTT in their corticospinal tracts but not in their somatosensory tracts and posterior thalamic radiations. In addition, the number and volume of fibers, but not fractional anisotropy values or apparent diffusion coefficients, are lower in the corticospinal tracts in children with low gross motor function than in those with high gross motor function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
47
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(55 citation statements)
references
References 28 publications
4
47
0
4
Order By: Relevance
“…8 Studies also have shown parametric changes that suggest secondary (Wallerian) neurodegeneration distant from the primary lesion site, with decreased FA and axial diffusivity (the largest tensor eigenvalue), increases in radial diffusivity (the mean of the 2 smaller tensor eigenvalues), but no changes or only slight increase in MD. 5,9 Moreover, the overall severity of CP, measured by, for example, the Gross Motor Function Classification System, 10 appears to correlate with diffusion parameters in motor 9,[11][12][13] and/or sensory pathways. [14][15][16] In addition, correlations have been shown between diffusion measures in motor and sensory tracts and specific measures of sensory and/or motor functions.…”
mentioning
confidence: 99%
“…8 Studies also have shown parametric changes that suggest secondary (Wallerian) neurodegeneration distant from the primary lesion site, with decreased FA and axial diffusivity (the largest tensor eigenvalue), increases in radial diffusivity (the mean of the 2 smaller tensor eigenvalues), but no changes or only slight increase in MD. 5,9 Moreover, the overall severity of CP, measured by, for example, the Gross Motor Function Classification System, 10 appears to correlate with diffusion parameters in motor 9,[11][12][13] and/or sensory pathways. [14][15][16] In addition, correlations have been shown between diffusion measures in motor and sensory tracts and specific measures of sensory and/or motor functions.…”
mentioning
confidence: 99%
“…It is a tool to approach microstructural networks, capable to provide a threedimensional visualization tool of nerves and muscles fibers (4).…”
mentioning
confidence: 99%
“…Of the 20 studies (91%) that used ROI placement, 17 (77%) used manual placement, whereas three (14%) used automatic parcellation 48,74,75 . Only six (35%) of the studies using manual ROI placement included reliability analysis 65,66,71,[76][77][78] .…”
Section: Imaging Parametersmentioning
confidence: 99%
“…There were on average 1.6 males to each female. Four studies (18%) included participants with spasticity in any motor distribution 67,72,75,80 ; 14 studies (64%) investigated specific motor distributions of spasticity, including seven (32%) of children with spastic hemiplegia 48,64,65,[68][69][70]81 ; two studies (9%) of children with spastic diplegia 66,73 ; three studies (14%) of children with spastic quadriplegia 60,71,82 , one study of children with bilateral spasticity 77 ; and one study comparing spastic quadriplegia with diplegia 79 .…”
Section: Participants and Clinical Measuresmentioning
confidence: 99%
See 1 more Smart Citation